A Collection of Medieval Seals from the Fortress Kale in Skopje, Excavated between 2007 and 2012 - Mihajlovski, Robert (Byzantion, 2016)
The following catalogue deals with the medieval seals uncovered during the archaeological excavation between 2009 and 2012 at the 'Kale' fortress in Skopje. The Byzantine seals found in the fortress are the largest collection of such items in the Republic of Macedonia. This collection of some eighty seals represents an important and authentic epigraphic source that sheds additional light on the history of Byzantine and Ottoman Skopje and its surroundings. Allthough some of the seals are damaged and hard to decipher, all are included in this survey as part of the collection, which relates to the life of the Kale fortress.